Effect of Cu insertion on structural, local electronic/atomic structure and photocatalyst properties of TiO2, ZnO and Ni(OH)(2) nanostructures: XANES-EXAFS study - Sharma, Aditya; Varshney, Mayora; Shin, Hyun Joon; Lee, Byeong hyeon; Chae, Keun Hwa; Won, Sung Ok (ELSEVIER SCIENCE SA, 2017)
We report detailed investigations on the synthesis, structural, morphology, electronic/atomic structure and photocatalyst properties of Cu doped TiO2, ZnO and Ni(OH)(2) nanostructures. All of the samples were synthesized by using the chemical precipitation method. Samples were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray absorption near edge structure (XANES), extended X-ray absorption fine structure (EXAFS) and photocatalyst measurements. XRD studies revealed single phase nature of the samples and omitted the presence of trivial metallic or binary oxide phases. TiO2 set of samples have shown nanorod kind of morphology, however TEM images of ZnO and Ni(OH)(2) set of samples depicted the spherical morphology of particles. XANES spectra at the Cu K-edge and Cu L-edge, along with the atomic multiplet calculations, revealed the predominance of Cu2+ ions in all of the samples, within the entire doping range. Ti L-edge and Ti K-edge XANES confirmed the existence of Ti4+ ions in the pure and Cu doped TiO2 samples with anatase local structure. Zn L-edge XANES results confirmed the divalent character of Zn ions in the pure and Cu doped ZnO, which is further validated by the Zn K-edge XANES. Ni L-edge and Ni K-edge XANES conveyed the +2 valence state of Ni ions in the pure and Cu doped Ni (OH)(2) samples. EXAFS analysis at the Cu K-edge nullifies the formation of Cu metallic clusters and other trivial phases, suggesting random distribution of Cu atoms in the oxide materials. Though, local atomic arrangement of Cu ions is disparate in the different oxide compounds. As an application of the pure and Cu doped TiO2, ZnO and Ni(OH)(2) nanostructures, towards the degradation of water pollutant dyes, we demonstrate that all of the samples can serve as effective photocatalyst materials towards the degradation of methyl orange aqueous pollutant dye under the UV-light irradiation. (C) 2017 Elsevier B.V. All rights reserved.